The Opioid-Sparing Effect of Perioperative Dexmedetomidine Combined with Oxycodone Infusion during Open Hepatectomy: A Randomized Controlled Trial - Zhang, Benhou; Wang, Guifang; Liu, Xiaopeng; Wang, Tian-Long; Chi, Ping (Frontiers in Pharmacology, 2018)
Background: A large right subcostal incision performed by open hepatectomy is associated with significant postoperative pain and distress. However, postoperative analgesia solutions still need to be devised. We investigated the effects of intra- and post-operative infusion of dexmedetomidine combined with oxycodone during open hepatectomy. Methods: In this prospective, randomized and double-blind investigation, 52 patients undergoing selective open hepatectomy were divided into dexmedetomidine (Dex) group (DEX infusion at an initial loading dose of 0.5 μg·kg-1 over 10 min before intubation then adjusted to a maintenance dose of 0.3 μg·kg-1·h-1 until incision suturing) or control (Con) group (0.9% sodium chloride was administered). Patient-controlled analgesia was administered for 48 h after surgery (Dex group: 60 mg oxycodone and 360 μg DEX diluted to 120 ml and administered at a bolus dose of 2 ml, with 5 min lockout interval and a 1 h limit of 20 ml. Con group: 60 mg oxycodone alone with the same regimen). The primary outcome was postoperative oxycodone consumption. The secondary outcomes included requirement of narcotic and vasoactive drugs, hemodynamics, incidence of adverse effects, satisfaction, first exhaust time, pain intensity, and the Ramsay Sedation Scale. Results: Postoperative oxycodone consumption was significantly reduced in Dex group from 4h to 48 h after surgery (P<0.05). Heart rate in Dex group was statistically decreased from T1 (just before intubation) to T6 (20 min after arriving at the postanesthesia care unit), while mean arterial pressure was significantly decreased from T1 to T3 (during surgical incision) (P<0.05). The consumption of propofol and remifentanil were significantly decreased in Dex group (P<0.05). The VAS scores at rest at 1, 4, and 8 h and with cough at 24, and 48 h after surgery were lower, the first exhaust time were shorter, satisfaction with pain control was statistically higher and the incidence of nausea and vomiting was less in Dex group than in Con group (all P<0.05). Conclusions: The combination of DEX and oxycodone could reduce oxycodone consumption and the incidence of nausea and vomiting, enhance the analgesic effect, improves patient satisfaction and shorten the first exhaust time.